2024
DOI: 10.3389/fpls.2023.1322719
|View full text |Cite
|
Sign up to set email alerts
|

Limited effects of plant-beneficial fungi on plant volatile composition and host-choice behavior of Nesidiocoris tenuis

Caroline Meesters,
Berhane T. Weldegergis,
Marcel Dicke
et al.

Abstract: Biological control using plant-beneficial fungi has gained considerable interest as a sustainable method for pest management, by priming the plant for enhanced defense against pathogens and insect herbivores. However, despite promising outcomes, little is known about how different fungal strains mediate these beneficial effects. In this study, we evaluated whether inoculation of tomato seeds with the plant-beneficial fungi Beauveria bassiana ARSEF 3097, Metarhizium brunneum ARSEF 1095 and Trichoderma harzianum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Although several studies have reported beneficial microbe-mediated effects on plant VOC emissions [ 17 , 72 , 73 ], in some cases the differences are only marginally significant [ 28 ], or the VOC analysis cannot explain the behavioural data [ 74 ]. Surprisingly, in our study we did not detect any significant differences in the VOC profiles between oviposition-exposed and control plants.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have reported beneficial microbe-mediated effects on plant VOC emissions [ 17 , 72 , 73 ], in some cases the differences are only marginally significant [ 28 ], or the VOC analysis cannot explain the behavioural data [ 74 ]. Surprisingly, in our study we did not detect any significant differences in the VOC profiles between oviposition-exposed and control plants.…”
Section: Discussionmentioning
confidence: 99%